Burrowing owl nest distribution and density in relation to urban development. Issue 3 (3rd May 2020) - Baladrón, Alejandro V.; Cavalli, Matilde; Isacch, Juan P.; Bó, María S.
Abstract : The effect of urbanization on birds typically has been evaluated through comparison of species composition between natural and urbanized habitats. However, few studies have examined the changes in species abundance as an urban area grows. During a 5-year period, we monitored two populations of burrowing owls ( Athene cunicularia ) nesting in separate urban areas with contrasting development and evaluated the tolerance of this species to increasing urbanization. The study was carried out in two small touristic coastal villages: Mar Chiquita and Camet Norte (Buenos Aires Province, Argentina). We digitalized satellite images and evaluated the interannual advance of the urbanized area at each village while simultaneously recording the changes in the number and location of burrowing owl nests. During the study period, the area occupied by buildings showed a slight change in Mar Chiquita (+ 17%) and a great expansion in Camet Norte (+ 269%). However, the number of owl nests increased in similar proportion in Mar Chiquita (+ 25%) and Camet Norte (+ 26%), and the maximum nest density was also similar for both villages (~ 0.14 nests/ha). Our results indicate that, unlike many raptors that are negatively affected by urbanization, burrowing owls may not be adversely impacted by nesting in areas with moderate levels of urban development.